PENERAPAN METODE SCM PADA SISTEM INFROMASI STOCK BARANG BERBASIS WEB (Studi Kasus: Konveksi Blackone) - teddy supriyadi; dadang hamdani (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2018)
Konveksi Blackone is a cloth maker company in the Cikijing District area - Majalengka and it is located in Sukamukti village, Sukaraos block. The problem faced by this company is the uncontrolled stock of goods both raw materials and finished goods so that it disrupts the stability of the company itself. on the system is running, the company is not controlling the stock of goods both raw materials and finished goods so that it disrupts the stability of the company itself. Customers also have difficulty in getting the goods ordered. Then in the process of recording the goods carried out manually either the data of the goods, recording records or recording the reports. Because data collection in processing data is still recorded manually so it is less effective in processing information. After going through various stages of testing design and implementation of the SCM method for Web-based Information Stock Information Systems on Blackone Convection, it can facilitate the company to manage the inventory process of raw material requirements, production processes and distribution of goods and increase the effectiveness of delivering information in the form of reports. This system encourages the efficiency of costs that must be spent by the company in every process carried out both the order process of products, raw materials, production and distribution of goods, this is because the distribution of goods for the company is easier and so is production.